Projeto Especial de Ação – PEA: significações construídas e compartilhadas por um grupo de professoras - Silva, Maria Daiane Cavalcante da (2019)
In this dissertation, we have aimed at understanding meanings constructed and shared by teachers about the Action Special Project (Projeto Especial de Ação – PEA), the main instrument for teachers’ continuous education in the city of São Paulo (PMSP). This study has been inspired by the postulates of a Critical-Collaborative Research – PCCol, whose interest if to intervene in school contexts by highlighting the researcher’s active role, in order to organize the collaborative research in a critical, transforming way, thus allowing participants to trace new paths for the work that is developed at school. References are based on Social, Historical and Cultural Theory, notably on the concepts of senses and meanings. Regarding methodology, research objectives were to: (1) analyze which senses and meanings have been shared by teachers during PEA; (2) confront theses meanings with the Decree which regulate the Project, and with the theoretical references of this research; (3) present critical-collaborative educational principles from the teachers’ perspectives. The study has been carried out in an EMEI – Escola Municipal de Educação Infantil (School for Children’s Education) located in Campo Limpo, a neighborhood in the South Zone of São Paulo. Subjects were 18 Children’s Education teachers. Instruments of production and collection of data were semi-structured questionnaires and interviews, which have been interpreted according to Bakhtin’s Dialogical Discourse Analysis and based on authors who discuss teachers’ education. Results have pointed out that PEA provides teachers with an important space for continuous education. Meanings constructed by the participants of this study towards PEA allow us to conclude that learnings resulted from the Project may reverberate in teachers’ practices. The teachers, however, have pointed out that the methodology used in the weekly education meetings is often tiresome and tedious, which reveals the importance to reconsider education strategies and to foster teachers’ education through an even more critical-collaborative perspective, as predicted by Liberali in her studies about PCCol